The relationship between blood pressure and environmental exposure to lead and cadmium in Belgium. - Staessen, J (1988)
The question whether in the general population environmental exposure to lead and cadmium influences blood pressure after controlling for confounding factors remains debated. The environmental exposure of the Belgian population to both lead and cadmium is high as compared with other countries. The Cadmibel Cooperative Study was therefore designed to elucidate whether environmental exposure to lead and cadmium has any effect on blood pressure and renal function in the population at large. Before embarking on the large Cadmibel project, a small study was conducted. Blood pressure and the 24-hr urinary excretion of cadmium (CdU) and lead (PbU) were determined in a random 4% sample of the population of a small Belgian town. CdU averaged 0.27 micrograms/24 hr in 46 youths (mean age 14 +/- 3 years, +/- SD), increased with age, and was higher in 57 adult men (age 41 +/- 14 years), as compared with 59 adult women (age 39 +/- 14 years) (1.05 vs. 0.81 micrograms/24 hr; p less than 0.01). PbU averaged 5.8 micrograms/24 hr in youths and similarly increased with age; adult men excreted more lead than women (13.3 vs. 8.3 micrograms/24 hr; p less than 0.001). Among men, manual workers excreted more cadmium (1.4 vs. 0.8 micrograms/24 hr; p less than 0.05) but a similar amount of lead (7.0 vs. 6.9 micrograms/24 hr) as compared with office workers. In simple regression analysis, CdU was positively correlated with both systolic (r = 0.30; p less than 0.05) and diastolic (r = 0.38; p less than 0.01) blood pressure in women.(ABSTRACT TRUNCATED AT 250 WORDS)